(untitled) (Bangladesh Journal of Neurosurgery, 2026)
Background: : Spontaneous cerebellar hemorrhage (SCH) is a potentially life-threatening condition that results in early neurological deterioration, significant disability, and adverse consequences. Therefore, knowledge of the factors that potentially affect the outcome is crucial for a sound clinical decision-making framework and for implementing efficient therapeutic measures. Objectives: This study aimed to identify possible clinical, radiological, and therapeutic factors associated with 30-day outcomes in patients with acute SCH. Materials and Method: Sixty-six computerized tomography (CT) diagnosed cases of SCH above 18 years of age who were admitted and managed in the Department of Neurosurgery of Chittagong Medical College Hospital from October 2021 to September 2022 were enrolled prospectively in this study based on inclusion and exclusion criteria. Data regarding demographic, clinical, radiographic, and treatment modalities was recorded. The 30-day outcome was assessed by the Glasgow Outcome Scale (GOS) score and analyzed. A poor outcome was defined by GOS ≤3. Results: The mean age was 65.6±10.8 years and 56.1% were male. The median Glasgow Coma Scale (GCS) score on admission was 13 [interquartile range (IQR) = 8-14]. Twenty-five patients (37.9%) underwent surgical management [evacuation of the cerebellar hemorrhage and placement of an external ventricular drain (EVD) in 7 (28%); EVD alone in 12 (48%), and only evacuation in 6 (24%) cases of surgically managed] and 41 (62.1%) were treated conservatively. The 30 day mortality rate was 36.4%. Regarding 30-day outcomes, 47% (31) of patients had a poor outcome after 30 days. On univariate analysis, GCS score on admission, hematoma size, hematoma volume, ventricular extension, 4th ventricle obstruction, hydrocephalus, tight posterior fossa, ratio between transverse diameter of cerebellar hematoma and posterior fossa, intervention type, and need for mechanical ventilation were significantly associated with 30-day poor outcome. In multivariate analysis, only the GCS score on admission was a significant predictor of a 30 day poor outcome [odds ratio (OR) = 0.28; 95% confidence interval (CI) = 0.12–0.66; P = 0.003]. For prediction of a 30 day poor outcome, receiver operating characteristic (ROC) curve analysis confirmed that the best cut off point was a GCS score of 11 on admission [area under the curve (AUC): 0.94, 95% CI = 0.88–0.98, P < 0.001] with the sensitivity of 94.3% and specificity of 87.1%. Conclusion: The 30-day outcome of SCH patients mostly depends on admission GCS score. A higher GCS score on their admission is strongly associated with a 30-day favorable outcome. Keywords: 30 day mortality, Cerebellar Hemorrhage, Outcome, Factors Associated with Cerebellar Hemorrhage Bang. J Neurosurgery 2024; 14(1): 3-12